The unavailable quota (forced share) and international public policy - Moura Ramos, Rui Manuel (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The contribution deals with the question whether lack of protection by applicable succession law of what is considered, by the lex fori, an unavailable quota (forced share) must be considered against public policy (ordre public international). After mentioning the position of several legal orders on the topic, the stand is taken that a general and fixed answer is not possible to this question, also given the exceptionality that is characteristic of this institute, but that the mere fact of non recognition of forced shares (reserve) may not as such (in se) be viewed as violating public policy, even if in certain circunstances (for example, when it leads to total exclusion of descendant minors without other means of existence from the assets of the deceased) a different answer could be provided. The discussion also includes a critique of some legal reforms that try to reach the same result achieved by public policy using substantive rules of private international law.